Triglyceride–glucose index change and chronic kidney disease progression in a Chinese hypertensive population - Yu, Chao; Shi, Yumeng; Wang, Tao; Zhu, Lingjuan; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2024)
Background The impact of triglyceride–glucose (TyG) index variations on chronic kidney disease (CKD) progression remains unexplored. To investigate the effects of the TyG index and its dynamic changes on CKD progression. Method This prospective cohort study included data from 8,418 hypertensive participants. The exposure variable in this study was defined as the difference between the TyG index at the last visit from that at baseline. The study’s outcome variable was the progression of CKD, defined as follows: for subjects with an estimated glomerular filtration rate (eGFR) ≥60 mL/min, a ≥30% decrease in eGFR with a final follow-up value <60 mL/min; for those with an eGFR <60 mL/min, a ≥50% decrease in eGFR; or terminal renal failure requiring dialysis. Results During a median follow-up period of 48 months, 1077 patients were diagnosed with CKD progression. In the fully adjusted Model 3, patients with a change in the TyG index <0 exhibited a significantly decreased 13% risk of CKD progression (HR: 0.87, 95% CI: 0.76–0.98) compared to those with a change in the TyG index≥0 group. Subgroup analyses showed that changes in the TyG index significantly increased the risk of CKD progression only in patients with diastolic blood pressure (DBP) <90mmHg. In the path analysis, baseline TyG was associated with follow-up eGFR (the standard regression coefficient was 1.26 [95% CI, 0.45–2.06]). Conclusions Our findings suggest that TyG variability may serve as a useful tool for identifying individuals at risk of CKD progression, particularly hypertensive patients with normal DBP levels.